Biblical women in early modern literary culture, 1550-1700 : 1550-1700. - Brownlee, Victoria; Gallagher, Laura (Oxford : Manchester University Press, 2016)
At once pervasive and marginal, appealing and repellent, exemplary and atypical, the women of the Bible provoke an assortment of readings across early modern literature. Biblical women in early modern literary culture, 1550-1700 draws attention to the complex ways in which biblical women's narratives could be reimagined for a variety of rhetorical and religious purposes. Considering a confessionally diverse range of writers, working across a variety of genres, this volume reveals how women from the Old and New Testaments exhibit an ideological power that frequently exceeds, both in scope and s.
8. Overview: Reading New Testament women in early modern England, 1550-1700: Victoria Brownlee and Laura Gallagher9. Christ's tears and maternal cannibalism in early modern London: Beatrice Groves; 10. Mary of recusants and reform: literary memory and defloration: Thomas Rist; 11. Stabat Mater Dolorosa: imagining Mary's grief at the cross: Laura Gallagher; 12. St Helena of Britain in the land of the Magdalene: All's Well That Ends Well: Lisa Hopkins; 13. Imagining the enemy: Protestant readings of the Whore of Babylon in early modern England, c.1580-1625: Victoria Brownlee.
Print version record.
14. Afterword: Dympna CallaghanIndex.
Includes bibliographical references and index.
Master record variable field(s) change: 072, 630, 650 - OCLC control number change
Keywords: Bible -- Criticism, interpretation, etc. -- History -- 16th century; Bible -- Criticism, interpretation, etc. -- History -- 17th century; Bible; Women in the Bible; Women in the Bible; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Women in the Bible; HISTORY / Europe / Russia & the Former Soviet Union; 1500-1699; Electronic books; Criticism, interpretation, etc; History